Examining Factors Influencing Indonesian Customer's Intention and Adoption of BOPS Service - Dita Kartika Sari; Rizal Edy Halim (Proceeding of International Conference on Global Innovation and Trend in Economics, 2022)
This study aims to identify the factors influencing customers' intention and adoption of the Buy Online Pick-up in Store (BOPS) service in Indonesia. The factors examined in this study are based on the Unified Theory of Acceptance and Use of Technology (UTAUT) and expanded with additional dimensions. The research surveyed 340 existing BOPS customers in Indonesia. Hedonic motivation, compatibility, price-saving orientation, personal innovativeness, and trust are predictors of the customer's intention to use the BOPS service in the future. Moreover, trust and behavior intention was found to be the factors that influence customers to adopt BOPS service. Meanwhile, performance expectancy, effort expectancy, and social influence do not significantly influence customers' intention to use the BOPS service. The output of this study adds the existing knowledge that explains customer behavior, BOPS explicitly as one of omnichannel service.